Memoirs of the Court of Marie Antoinette, Queen of France, Volume 5 : Being the Historic Memoirs of Madam Campan, First Lady in Waiting to the Queen - Campan, Mme. (Jeanne-Louise-Henriette), 1752-1822 (Salt Lake City, UT : Project Gutenberg, 2004)
"Memoirs of the Court of Marie Antoinette, Queen of France, Volume 5" by Mme. Campan is a historical account likely written in the early 19th century. This volume recounts the tumultuous events surrounding the French Revolution from the perspective of Marie Antoinette$1 (Bs First Lady in Waiting, offering insight into the Queen$1 (Bs experiences and the mounting political unrest in France. It chronicles the intricate dynamics at court, the challenges faced by the monarchy, and the profound emotional turmoil experienced by Marie Antoinette amidst the rising tide of revolution. At the start of this volume, the narrative unfolds against the backdrop of significant historical events, such as the oath taken at the Tennis Court and the ensuing royal assembly. The opening scenes depict the Queen's strong emotional responses to political maneuvers, particularly regarding M. Necker$1 (Bs actions and the increasing animosity toward the royal family. Mme. Campan portrays the escalating tensions of a nation in turmoil, as seen through the uneasy interactions between the Queen and the populace. This portion sets the stage for the dramatic and tragic events that will unfold, revealing the deep loyalty of the Queen's supporters, her personal relationships, and the impending challenges that threaten the monarchy$1 (Bs survival. (This is an automatically generated summary.)s
Release date is 2004-12-04
Produced by David Widger
Keywords: France -- Court and courtiers; Marie Antoinette, Queen, consort of Louis XVI, King of France, 1755-1793